Avaliação da atividade gastroprotetora do estragol em modelos animais - Alves Júnior, Edvaldo Balbino (2019)
Estragole is an aromatic organic compound belonging to the class of phenylpropanoids derived from cinnamic aldehydes present in essential oils of plant species such as Ravensara anisata (madeira), Ocimum basilicum (manjericão/alfavaca) and Croton zehntneri (canelinha). Pharmacological studies report its anti-inflammatory, antioxidant and vasorelaxant activity. This study aimed to evaluate acute non-clinical toxicity, gastroprotective activity and related mechanisms of action. The assay was considered significant when p<0.05. In the acute toxicity test, doses of 300 or 2000 mg/kg of estragole administered orally did not observed, except for a dose of 2000 mg/kg with a decrease in water consumption and feed. In this way, it was possible to estimate that the 50% lethal dose (LD50) is equal to or greater than 2500 mg/kg, according to OECD guide 423. For the evaluation of gastroprotective activity, the models of acute gastric ulcer induction by ethanol in rats, non-steroidal anti-inflammatory (NSAIDpiroxicam) and stress (cold restraint) in mice and gastric juice contention in rats were used. In the ethanol model, carbenoxolone (100 mg/kg) and estragol (31.25, 62.5, 125 and 250 mg/kg - vo) reduced the area of ulcerative lesion in 55, 25, 69, 74, 95% (***p<0.001), respectively, when compared to the negative control. In addition, the most effective dose (250 mg/kg) improved the histological parameters evaluated. In stress - induced gastric ulcers (cold restraint), cimetidine (100 mg/kg) and estragol (31.25, 62.5, 125 and 250 mg/kg - vo) reduced the ulcerative lesion index (ULI) in 42, 45, 53, 59, 65% (**p<0.01) and (***p<0.001), respectively, when compared to the negative control. In gastric ulcers induced by NSAIDs, cimetidine (100 mg/kg) and estragol (31.25, 62.5, 125 and 250 mg/kg - vo) reduced ULI by 59, 46, 47, 56 and 64% (***p<0.001), respectively when compared to the negative control group. Cimetidine (100 mg/kg) and estragol (250 mg/kg) reduced the ILU by 42 and 52% (v.o) (***p<0.001) in gastric ulcer induced by pylorus ligation and in 42 and 43% (i.d) (###p<0.001), respectively. In order to investigate the mechanisms involved in the gastroprotective activity of estragole, the antisecretory or neutralizing of gastric secretion, cytoprotection, antioxidant and immunoregulatory mechanisms were evaluated. Pylorus ligation (i.d) treatment with estragol (250 mg/kg) decreased the volume of the gastric juice. The gastroprotective activity of estragol (250 mg/kg) involves the participation of sulfhydryl groups, nitric oxide, mucus and prostaglandins. It increased levels of reduced glutathione (GSH) and glutathione peroxidase (GPx) and reduced levels of malondialdehyde (MDA) and myeloperoxidase. It reduced the levels of interleucin-1 beta (IL-1β), tumor necrosis factor alpha (TNF-α) and inducible nitric oxide synthase (iNOS) expression, and increased levels of interleucin-10 (IL- 10) and cyclooxygenase 2 (COX-2). Thus, it is possible to infer that estragole has gastroprotective activity related to antisecretory mechanisms, cytoprotectors, antioxidants and immunomodulators.